Severe drug reaction with eosinophilia and systemic symptoms with acute liver failure managed with therapeutic plasma exchange: case report - Sharan, Kshitiz; Jain, Tanmay (International Journal of Research in Medical Sciences, 2023)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a drug reaction which is associated with systemic symptoms. The exact pathogenesis is not known but may be related to drug specific immune response. The severity of disease varies from mild skin eruptions with transaminasemia to life threatening organ failure. Liver is the most common organ involved. However, acute liver failure is less common. Once liver failure develops patients need liver transplant. Transplant is not always feasible. We present a case report of a middle-aged male who presented with phenytoin induced DRESS and acute liver failure. He was salvaged with low volume plasma exchange; 1.5 to 2 times of patient’s plasma volumes was replaced with fresh frozen plasma. This new and novel technique has no major side effects can be life-saving in situations where the patient cannot undergo a transplant.